The liberalism is one and trino. Hayek, Bobbio and Berlin (2010)
The author shows in this text the faces of liberalism when it tries to make compatibles, incompatibles or absolutes the liberal values of liberty and equality. In particular, put forward the contrast between the arguments of an author that, considering li